Power Relations in the Stadium Stands: Strengthening Gender Equality in Indonesian Football Club Supporters - Bayu Mitra A. Kusuma; Theresia Octastefani (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2022)
Football competition in Indonesia is commonly perceived as male-dominated supporters. However, there is a growing trend of women supporters' groups. This study aims to analyze the hierarchical and power relations between women and men members of Brigata Curva Sud (BCS), a supporter base of PSS Sleman football club, which in 2017 was praised as the best ultra supporter in Asia. The study uses a descriptive-qualitative methodology to analyze the phenomenon. Using Michel Foucault's theory of power relations, the research findings demonstrate that BCS's manifesto is